(3GdahGFO GdNGbGfjI GdCMeOjIs - (3GdTQhGfj , eMeO Gejf Hf UOQGdOjf GdTQhGfj,J (B1036 (3g` s
(3ChdgG (B:s
,(3HYO ajbhd eMeO GdTQhGfiEf CQaY GdeWGdH hCSfGgG hCfaY GdeCQH hCYdGgG eG fWb Hg GdcJGH hGdSfI s
(3BNQgG (B:s
(3hfSCd Gddg Cf jOaY Yf GdOhdI GdYKeGfjI gPg GdYdGeGJ hdjcf gPG BNQ eG ChQOfG EjQGOg efg OQQ GdahGFO hZQQ GdaQGFO s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B41 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B73s
Keywords: (3GdeYGQa GdYGeIs